2012
DOI: 10.7598/cst2013.302
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Performance and Adsorption Behavior of Spinacia Oleracea Leaves Extracts on Mild Steel Corrosion in Hydrochloric Acid Medium

Abstract: Alcoholic extracts of Spinach (SP) leaves was studied as corrosion inhibitor for mild steel in 0.5 M HCl using weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy techniques. The results of the study revealed that SP extracts inhibit mild steel corrosion through adsorption process following Langmuir adsorption isotherm. The protection efficiency increased with increase in inhibitor concentration and decreased with temperature. Polarization measurements indicated that the SP beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…It was shown that the rate of steel corrosion increased with temperature for a particular OPE and OPE-CuO NPs concentration. Additionally, the outcomes obtained showed that the investigated OPE had an inhibitory effect at the evaluated temperatures, and that the extract inhibitor's efficiency was temperature-dependent, and that the percentage decreased as the temperature increased due to physisorption [53][54][55].…”
Section: Figure 6 the Variation Of η%Of Ope-cuo Nps On Carbon Steel W...mentioning
confidence: 97%
“…It was shown that the rate of steel corrosion increased with temperature for a particular OPE and OPE-CuO NPs concentration. Additionally, the outcomes obtained showed that the investigated OPE had an inhibitory effect at the evaluated temperatures, and that the extract inhibitor's efficiency was temperature-dependent, and that the percentage decreased as the temperature increased due to physisorption [53][54][55].…”
Section: Figure 6 the Variation Of η%Of Ope-cuo Nps On Carbon Steel W...mentioning
confidence: 97%
“…Above 1200 ppm, the corrosion rate approximately remained constant. The constant rate obtained could be attributed to the competitive adsorption effect between inhibitor molecules and the metal surface which is already covered with initial layers of molecules [22]. The % IE at different concentrations of AA extracts decreases with increasing temperature from 303 K to 333 K ( Figure 1).…”
Section: Mass Loss Studiesmentioning
confidence: 98%
“…The refluxed solution was filtered using No.1 Whatman filter paper and heated on a water bath to evaporate the water content until a dried component was obtained. [15,24] For the preparation of DILE inhibitor, dried extract about 30, 60, 90, and 120 mg was used in 100 mL of 1 M NaOH to obtain 300, 600, 900, and 1200 ppm of (0.3, 0.6, 0.9, and 1.2 g/L) concentrations for corrosion studies.…”
Section: Preparation Of Derris Indica Leaves Extract (Dile)mentioning
confidence: 99%